METODE NEW JERSEY UNTUK CADANGAN ASURANSI JIWA DWIGUNA DENGAN DISTRIBUSI GOMPERTZ - Ramlah Annuri; Tumpal P. Nababan; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the prospective premium reserve modified using New Jersey method on endowment insurance. This method limits calculation of reserves for 20 years. The calculations of the endowment insurance reserve is solved by priordetermination of the annuity, single premium, and annual premium based on the distribution of Gompertz.